PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAS PETERNAKAN DAN PERIKANAN KABUPATEN GROBOGAN - Setyo Wahyuningsih; Sudarmadi Sudarmadi; Triyanto Triyanto (STIE Atma Bhakti, 2021)
This study purposes were determined the effect of leadership, work environment, work discipline and motivation on employee performance at the Dinas Peternakan dan Perikanan, Grobogan Regency. The research type is a survey research using a questionnaire as the instrument. The research population are employees at the Dinas Peternakan dan Perikanan, Grobogan Regency. The sample used in this study amounted to 62 respondents. Data collection technique used questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The research results shown that there is a positive and significant effect of leadership, work environment, work discipline, and work motivation on employee performance both individually and simultaneously. Leadership is the variable with the most dominant effect on the performance of the employees of the Dinas Peternakan dan Perikanan in Grobogan Regency.